Topical and intraluminal Carolina Rinse Solution in p44/42 and p38 MAP Kinase activation profile in rabbit jejunum after ischemia and reperfusion - Luciana Ramos Gaston Brandstetter; Eugênio Gonçalves de Araújo; Juan Carlos Duque Moreno; Maria Clorinda Soares Fioravanti; Veridiana Maria Brianezi Dignani de Moura; Patrícia de Almeida Machado (Ciência Rural, 2014)
The effects of topical and intraluminal Carolina Rinse Solution (CRS) in p44/42 (ERK 1/2) and p38 MAPK activation profile, in rabbit jejunum after ischemia and reperfusion (I/R), were investigated in this study. Fifteen New Zealand rabbits were allocated in three groups: Sham-operated (A), Ischemia and reperfusion (B) and CRS (C). Groups B and C were subjected to one hour of ischemia and two hours of reperfusion. In group C, ten minutes prior to reperfusion, the bowel lumen was filled with CRS, and the segment was immersed in CRS until reperfusion onset. Ischemia and reperfusion stimulated the phosphorylation of the p44/42 MAPK and p38 MAPK pathways in some layers of jejunum. Progressive activation of p44/42 MAPK was chiefly localized in the crypts of Lieberkühn, circular and longitudinal muscle layers, whereas p38 MAPK was prominently activated in myenteric plexus and both muscle layers. The results of this research indicate that the chosen model of topical and intraluminal CRS does not interfere in p44/42 and p38 MAPK activation profile in rabbit jejunum subjected to I/R.